Rancang Bangun Website Company Profile Kelurahan Klapanunggal - Satria Putra, Rani Laple; Surya Agung Pramudya; Rikho Ariesky Rowardo; Muhammad Fitrah Maulana (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2024)
This research was carried out to build a Kelurahan website, with the aim of making it easier for the Klapanunggal community to obtain the most complete and up-to-date information, because information is very important in making decisions to achieve goals. Another aim is to increase ease of access to services in the sub-district. The method used is waterfall, which is known as a sequential approach from the planning, analysis, design, implementation, testing and maintenance stages. This approach can provide an organized structure in building a website, so that it can achieve the results required by the Village. The result of this research is a website that is user friendly, informative, and easily accessible to the general public. This website can be an effective means of increasing communication and transparency between sub-districts and their residents